Akibat Hukum Atas Perubahan Isi Akta Notaris Tanpa Persetujuan Para Pihak - Katinka Dyah Kusumawati; Budi Santoso; Adya Paramita Prabandari (Notarius, 2021)
A notary is usually considered an official from whom reliable advice can be obtained. However, in practice in the field, there are notaries who violate the provisions. This study aims to determine the accountability of the notary regarding changes to the contents of a notary deed without the consent of the parties and the legal consequences of changing the contents of a notary deed without the consent of the parties. This study used a normative juridical approach. The results of this study state that a notary who changes the contents of a notary deed without notification to either party, then the notary must be liable by being sentenced, but in terms of the strength of evidence, the original deed is degraded into an underhand deed because it has violated several articles contained in the law. -invited the position of notary public. The legal consequence of changing the authentic deed that does not meet the requirements causes huge losses to one of the parties involved in the implementation of the contract. Loss of a party due to an act against the law. Any violation of the law that changes actual behavior without informing the parties must be held accountable for administrative law, civil law and criminal law.Keywords: change; deed; Notary  AbstrakSeorang notaris biasanya dianggap sebagai pejabat dari siapa nasihat yang dapat diandalkan dapat diperoleh. Namun dalam praktek di lapangan, ada notaris  yang melanggar ketentuan. Penelitian ini bertujuan untuk mengetahui pertanggungjawaban notaris terkait perubahan isi akta notaris tanpa persetujuan para pihak dan akibat hukum terhadap perubahan isi akta notaris yang tanpa persetujuan para pihak. Penelitian ini menggunakan pendekatan yuridis normatif. Hasil dari penelitian ini menyatakan notaris yang mengubah isi akta notaris tanpa pemberitahuan kepada salah satu pihak maka notaris harus bertanggungjawab dengan dijatuhi hukuman, namun dari segi kekuatan pembuktiannya, yang semula akta autentik terdegradasi menjadi akta di bawah tangan karena telah melanggar beberapa pasal yang termuat dalam undang-undang jabatan notaris. Akibat hukum dari perubahan akta otentik yang tidak memenuhi persyaratan menyebabkan kerugian yang besar bagi salah satu pihak yang terlibat dalam pelaksanaan kontrak. Kerugian salah satu pihak akibat daru perbuatan melawan hukum. Setiap pelanggaran hukum yang mengubah perilaku yang sebenarnya tanpa memberitahu para pihak harus dimintai pertanggungjawaban atas hukum administrasi, hukum perdata, dan hukum pidana.Kata kunci: perubahan; akta; notaris